Plantas de cobertura associadas a fontes de adubação na recuperação inicial de área degradada pela mineração de bauxita em Barro Alto, GO - Silva, Átila Reis da (2014)
The mine bauxite Barro Alto is the first ore economically viable bauxite in the central- west region of Brazil and has peculiar characteristics. After mining, the chemical, physical and biological soil characteristics are unsuitable for replanting, making it difficult to environmental recovery. The aim of this study was to evaluate the use of green manure in organic and mineral fertilizer and their influence on the physical and chemical attributes of the area to be reclaimed and implementation of an agroforestry system. This work was developed in degraded area located at Barro Alto, Goias The study area has 5000 m2 and is in the process of recovery since February 2012. Two cycles of planting green manure the first in March 2012 were performed, and the second. In December 2012 the treatments were: 1- pigeonpea; 2- jack bean; 3- sunn hemp; 4- velvet bean; 5- milhet intercropping with faba bean; 6 - millet intercropped with beans pork; 7 - milhet intercropped with sunn hemp; 8- milhet intercropped with velvet bean and three nutrient sources: 1- fertilization with phosphate Arad; 2- the cattle manure; 3- mineral fertilizer controlled release fertilizers. Phytotechnical the characteristics of green manures (height, chlorophyll content, biomass production and nutrient accumulation ) , chemical properties (pH, macronutrients and soil organic matter) and physical soil (bulk density, macro and micropores, volume total pore, gravimetric moisture and penetration resistance ). An agroforestry system using three species, apeiba (pioneer), the baru (middle) and pequi (climaceaes) was implemented in February 2013. The results showed that 17.1% of the biomass originated in pearl millet indicating legumes are the main factors of increase in that variable. The use of mineral source (NPK) significantly increased the biomass of green manure, nutrient accumulation and plant height in relation to the Arad phosphate and manure. With the introduction of green manuring, the content of exchangeable soil Al, H + Al and Al saturation (m%) reduced by 55%, 18.46% and 37.47% in relation to beginning of recovery, respectively. The use of green manure increased the soil organic matter, base saturation and potassium in 156%, 41.71% and 52.41% in relation to beginning of recovery, respectively. The macro and microporosity, in addition to resistance to penetration, improved after 18 months of implementation of the recovery, demonstrating that cropping practices adopted for recovery of degraded in the study area is being active. After 270 days of planting of tree species cover crops and sources used did not influence the height and diameter. The apeiba excelled at increase in height and diameter than the baru and pequi.